Exploring Step‐by‐Step Assembly of Nanoparticle:Cytochrome Biohybrid Photoanodes. Issue 8 (15th May 2017) - Hwang, Ee Taek; Orchard, Katherine L.; Hojo, Daisuke; Beton, Joseph; Lockwood, Colin W. J.; Adschiri, Tadafumi; Butt, Julea N.; Reisner, Erwin; Jeuken, Lars J. C.
Abstract: Coupling light‐harvesting semiconducting nanoparticles (NPs) with redox enzymes has been shown to create artificial photosynthetic systems that hold promise for the synthesis of solar fuels. High quantum yields require efficient electron transfer from the nanoparticle to the redox protein, a property that can be difficult to control. Here, we have compared binding and electron transfer between dye‐sensitized TiO2 nanocrystals or CdS quantum dots and two decaheme cytochromes on photoanodes. The effect of NP surface chemistry was assessed by preparing NPs capped with amine or carboxylic acid functionalities. For the TiO2 nanocrystals, binding to the cytochromes was optimal when capped with a carboxylic acid ligand, whereas for the CdS QDs, better adhesion was observed for amine capped ligand shells. When using TiO2 nanocrystals, dye‐sensitized with a phosphonated bipyridine Ru(II) dye, photocurrents are observed that are dependent on the redox state of the decaheme, confirming that electrons are transferred from the TiO2 nanocrystals to the surface via the decaheme conduit. In contrast, when CdS NPs are used, photocurrents are not dependent on the redox state of the decaheme, consistent with a model in which electron transfer from CdS to the photoanode bypasses the decaheme protein. These results illustrate that although the organic shell of NPs nanoparticles crucially affects coupling with proteinaceous material, the coupling can be difficult to predict or engineer. Abstract : Biohybrid voltaics : The coupling between light‐harvesting semiconducting nanoparticles (NPs) with redox proteins has been studied to better understand artificial photosynthetic systems that hold promise for the synthesis of solar fuels. Contrasting behaviour was observed when decaheme proteins were coupled with either TiO2 nanocrystals, dye‐sensitized with a phosphonated bipyridine Ru‐(II) dye or CdS quantum dots.